Once upon a mind : the stories and scholars of gifted child education - DeLisle, James R. (Fort Worth : Harcourt Brace College, 2000)
This book is about Gifted Child Education; Identification of Gifted and Talented Children; The Creative Mind and Spirit; Curriculum, Instruction, and Program Planning for Gifted Students; Instructional Styles and Strategies; The Social and Emotional Needs of Gifted Individuals...
Keywords: Education; Gifted children; Gifted children -- Education